Factors Influencing Married Immigrant Women's Perceived Health Status: The National Survey of Multicultural Families 2012 - Ji Won Yun; Hee Sun Kang (Korean Society of Women Health Nursing, 2015)
PURPOSE: The purpose of this study was to investigate factors that influence married female immigrants' perceived health status. METHODS: This study was a retrospective review of dataset from the 2012 National Multicultural Family Survey in Korea. Data were analyzed using descriptive statistics, t-tests, an analysis of variance (ANOVA), Pearson correlation analysis, and multiple regression with the data of 3,014 married female immigrants. RESULTS: Multiple regression analysis showed that demographic factors (age, education level, nationality, period of residency in Korea, and residential area), socio-economical factors (monthly family income, employment, support from the government for basic living, and Medicaid), social support factors (marital conflict, satisfaction with family relationships, some one to talk about self or family matters, meeting with homeland friend, and participation in community meeting), and immigration factors (life satisfaction, experience of social discrimination, and difficulties with living and using medical care) were associated with perceived health status. CONCLUSION: It is important to pay closer attention to immigrant women who have low economic status, less social support, experience difficulties with living in Korea and using medical care. An effective support system for this population should be developed in order to help them successfully transition.